FORMATION OF STUDENTS’ CREATIVE ABILITIES ON THE BASIS OF INTERACTIVE TEACHING METHODS - Nasretdinova Feruza Nabievna (International Engineering Journal For Research & Development, 2021)
The article reveals the essence of creativity, the term creativity, social factors influencing the development of creative qualities, personal activity, methods and forms of the formation of critical, creative thinking in students, flexibility of thinking, criteria of creativity.